Advanced Construction Technology - Chudley, Roy; Greeno, Roger; Hurst, Mike; Topliss, Simon (Pearson Education Limited, 2012)
The authors provide a comprehensive and practical presentation to many aspects of construction practice, as applied to buildings for industrial and commercial purposes. The book covers site works, plant and equipment, substructure, demolition and temporary work, and much more.